Planet formation in self-gravitating discs - Gibbons, Peter George (The University of Edinburgh, 2013)
The work performed here studies particle dynamics in local two-dimensional simulations of self-gravitating accretion discs with a simple cooling law. It is well known that the structure which arises in the gaseous component of the disc due to a gravitational instability can have a significant effect on the evolution of dust particles. Previous results using global simulations indicate that spiral density waves are highly efficient at collecting dust particles, creating significant local over-densities which may be able to undergo gravitational collapse. This thesis expand on these findings, using a range of cooling times to mimic the conditions at a large range of radii within the disc. The PENCIL Code is used to solve the 2D local shearing sheet equations for gas on a fixed grid together with the equations of motion for solids coupled to the gas solely through aerodynamic drag force. The work contained here shows that spiral density waves can create significant enhancements in the surface density of solids, equivalent to 1-10cm sized particles in a disc following the profiles of Clarke (2009) around a solar mass star, causing it to reach concentrations several orders of magnitude larger than the particles mean surface density. These findings suggest that the density waves that arise due to gravitational instabilities in the early stages of star formation provide excellent sites for the formation of large, planetesimal-sized objects. These results are expanded on, with subsequent results introducing the effects of the particles self-gravity showing these concentrations of particles can gravitationally collapse, forming bound structures in the solid component of the disc.
Keywords: astronomy; astrophysics; planet formation; discs